2016
DOI: 10.1002/tox.22329
|View full text |Cite
|
Sign up to set email alerts
|

Role of NF‐κB activation and Th1/Th2 imbalance in pulmonary toxicity induced by nano NiO

Abstract: With the progress of nanotechnology, nano nickel oxide (NiO) has been extensively used as sensors, battery electrodes, catalysts, and cosmetics. Previous researches verified that nano NiO could exert pulmonary toxicity, but its mechanism was unclear. To shed light upon this, the role of nuclear factor-κB (NF-κB) activation and Th1/Th2 imbalance were to explore in pulmonary damage induced by nano NiO. Male Wistar rats were randomized into control group, nano NiO groups (0.015, 0.06, and 0.24 mg kg ) and micro N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 34 publications
0
40
0
2
Order By: Relevance
“…Thus, impaired redox balance may obviously lead to the activation of NF-κB. 39 Moreover, the generation of high levels of NO, followed by the rapid production of other reactive nitrogen species, which are the major components of oxidative stress, is often considered as an essential mechanism of nanomaterial toxicity. 40 Prolonged or excessive NO production has deleterious effects leading, among others, to serious endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, impaired redox balance may obviously lead to the activation of NF-κB. 39 Moreover, the generation of high levels of NO, followed by the rapid production of other reactive nitrogen species, which are the major components of oxidative stress, is often considered as an essential mechanism of nanomaterial toxicity. 40 Prolonged or excessive NO production has deleterious effects leading, among others, to serious endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Single intratracheal instillation of nano-NiO in rats induces oxidative stress, inflammatory response, collagen deposition, and apoptosis in lung tissues (6)(7)(8). In our previous studies, nano-NiO was demonstrated to result in lung lesions following intratracheal instillation for 6 weeks in rats and to enhance the nitrative stress and inflammatory response (9), an effect that was associated with nuclear factor-κB activation and T helper (Th)1/Th2 cell imbalance (10). Other reports have also demonstrated that nano-NiO induces toxicity in various cell lines, including human bronchial epithelial cells, type II human alveolar epithelial cells, human monocytes and mouse embryonic stem cells (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The average diameter of nano NiO suspended in 0.9% NaCl was 244.5 nm. Other details of physicochemical characteristic were presented in our previous studies …”
Section: Resultsmentioning
confidence: 99%
“…nano NiO group, and 0.24 mg/kg b.w. micro NiO group . Rats were intratracheally instilled samples suspension (1 mL/kg b.w.)…”
Section: Methodsmentioning
confidence: 99%